The CLARA/NORSAT-1 solar absolute radiometer: instrument design, characterization and calibration. (10th August 2017) - Walter, Benjamin; Levesque, Pierre-Luc; Kopp, Greg; Andersen, Bo; Beck, Ivo; Finsterle, Wolfgang; Gyo, Manfred; Heuerman, Karl; Koller, Silvio; Mingard, Nathan; Oliva, Alberto Remesal; Pfiffner, Daniel; et al.
Abstract: The compact lightweight absolute radiometer (CLARA) experiment aims at measuring the total solar irradiance (TSI) in space and is scheduled to fly on the Norwegian NORSAT-1 micro satellite. The CLARA experiment will contribute to the long term monitoring of the TSI variability to support the analysis of potential long term trends in the Sun's variability. CLARA is traceable to the National Institute of Standards and Technology radiometric scale and will provide further evidence for the TSI value on an absolute scale. In this paper we present the design, characterization, and calibration details of the CLARA instrument. The combined measurement uncertainty for the calibrated SI-traceable CLARA flight instrument is 567–912 ppm ( k = 1) depending on the measuring channel.